A novel evaluation of train running safety on the HSR bridges under earthquakes based on the observed track deformation rate. (15th January 2023) - Chen, Yuanjun; Jiang, Lizhong; Lai, Zhipeng; Li, Jing
Highlights: The friction pendulum bearing is insufficient to completely inhibit the risk of seismic derailment. The deterioration of the track geometry under earthquake led to the train derailment. The derailment coefficient has a high misjudgment rate of train derailment under earthquakes. The material derivative of the track deformation can be used as the lower limit for evaluating train running safety. Abstract: Safe operation of the trains on the high-speed railway bridge requires the railway line to have a high level of track regularity. High-speed railway bridges can deform unevenly under horizontal earthquakes, and the solid instantaneous deformation of the track can cause the train to derail. This paper develops a refined nonlinear model of the train-track-bridge coupling vibration subjected to seismic shaking to capture as comprehensively as possible the impact of the transient deformation of the track on the train operation at each moment and position. In addition, the risk factors and derailment characteristics are investigated in depth. The findings showed that the earthquake caused the bridge's girder ends to undergo severe dislocation and rotation, which facilitates the derailment of a train. Moreover, the vibration coupling between the train and the bridge becomes strong after bearing shear pin failure. Based on the statistical results of derailment causes, a novel index for evaluating the train running safety on the high-speed railway bridge is proposed. Besides, the engineering applications of this index are also introduced. Indeed, this new index can be used as the lower limit for evaluating train derailment on HSR bridges during earthquakes.